2017
DOI: 10.2135/cropsci2016.01.0031
|View full text |Cite
|
Sign up to set email alerts
|

QTL Identification for Brace‐Root Traits of Maize in Different Generations and Environments

Abstract: Elucidating the correlations among maize (Zea mays L.) brace‐root traits and identifying the quantitative trait loci (QTL) that control the traits are important for genetic improvement of brace‐root traits. Two maize inbred lines, Yi17 (well‐developed root system) and Yi16 (poorly developed root system), an F2 population derived from their cross containing 276 individuals, and an F2:3 population containing 241 families were used to analyze the correlations among brace‐root traits and determine the QTL for brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Although optimal brace root traits for root lodging-resistance have been identified, there are limited reports to define the genetic basis of these traits. The studies that have been reported primarily focus on the total number of brace root whorls [Zhang et al, 2018a, Ku et al, 2012, Gu et al, 2017, Zhang et al, 2018b, with only one study differentiating between the number of brace root whorls that enter the soil and the total number of brace root whorls [Ku et al, 2012]. In this study, an analysis of recombinant inbred line (ril) and immortalized F2 (if2) populations identified both shared and independent quantitative trait loci (qtl) for brace root whorls in the soil and the total number of brace root whorls [Ku et al, 2012].…”
Section: Genetic Regulation Of Brace Rootsmentioning
confidence: 99%
“…Although optimal brace root traits for root lodging-resistance have been identified, there are limited reports to define the genetic basis of these traits. The studies that have been reported primarily focus on the total number of brace root whorls [Zhang et al, 2018a, Ku et al, 2012, Gu et al, 2017, Zhang et al, 2018b, with only one study differentiating between the number of brace root whorls that enter the soil and the total number of brace root whorls [Ku et al, 2012]. In this study, an analysis of recombinant inbred line (ril) and immortalized F2 (if2) populations identified both shared and independent quantitative trait loci (qtl) for brace root whorls in the soil and the total number of brace root whorls [Ku et al, 2012].…”
Section: Genetic Regulation Of Brace Rootsmentioning
confidence: 99%
“…Although optimal brace root traits for root lodging-resistance have been identified, there are limited reports to define the genetic basis of these traits. The studies that have been reported primarily focus on the total number of brace root whorls (Gu et al, 2017;Ku et al, 2012;Zhang, et al, 2018a;Zhang, et al, 2018b), with only one study differentiating between the number of brace root whorls that enter the soil and the total number of brace root whorls (Ku et al, 2012). In this study, an analysis of recombinant inbred line (RIL) and immortalized F2 (IF2) populations identified both shared and independent quantitative trait loci (QTL) for brace root whorls in the soil and the total number of brace root whorls (Ku et al, 2012).…”
Section: Genetic Regulation Of Brace Rootsmentioning
confidence: 99%
“…Recently, several studies have attempted to examine the genetic basis of maize root system architectures in both field (Zaidi et al 2016;Gu et al 2017;Zhang et al 2018) and controlled conditions (Pace et al 2015a, b;Zurek et al 2015;Song et al 2016;Liu et al 2017;Sanchez et al 2018). However, most of those studies used relatively short time-point intervals and low-density marker genetic maps, resulting in large inter-marker intervals (Song et al 2016).…”
Section: Introductionmentioning
confidence: 99%